Emotion regulation and psychopathology: Investigating differential associations between emotion regulation skills and psychological symptoms using a network approach - Trautmann, Sebastian; Muehlhan, Markus; Berking, Matthias; Miethe, Sandra; Wigger, Janna; Dragan, Małgorzata (British Journal of Clinical Psychology, 2024)
Objectives: Emotion regulation plays an important role in the development and maintenance of psychopathology. However, the question whether specific ER skills are related to specific psychological symptoms has rarely been studied, but has important implications for targeted interventions. This analysis aims to explore potential differential associations between various ER skills and psychological symptoms using a network analysis approach. Methods: Routine data from a transdiagnostic clinical sample of 716 patients (460 females, 256 males) from an outpatient clinic for psychotherapy were analysed. Nine ER skills were assessed with the Emotion Regulation Skills Questionnaire, and nine symptom dimension scores were obtained using the Brief Symptom Inventory. A regularized partial correlation network models including ER skills and individual symptom domains were calculated. Bridge expected influence was calculated to estimate the strength of association of each ER skill with psychological symptoms. Results: Only the following ER skills were most strongly related to psychological symptoms (bridge expected influence): Tolerance, Confrontation and Modification. All other ER skills were indirectly connected to symptom severity through these four skills. The strongest direct edges between ER skills and symptoms were Modification—Depression, Confrontation—Obsession-Compulsion and Tolerance—Interpersonal Sensitivity, which were significantly stronger than the vast majority of other associations between ER skills and psychological symptoms. Conclusions: These exploratory findings provide valuable targets for future studies to investigate specific associations between ER skills and psychological symptoms which could help to improve outcome monitoring and efficacy of interventions targeting ER.
CRIS-Team Scopus Importer:2024-10-04
Keywords: emotion regulation; network analysis; psychological symptoms; psychopathology